2015
DOI: 10.1103/physreva.91.013845
|View full text |Cite
|
Sign up to set email alerts
|

Structure and symmetry in coherent perfect polarization rotation

Abstract: Theoretical investigations of different routes to coherent perfect polarization rotation illustrate its phenomeno logical connection with coherent perfect absorption. Our study of systems with broken parity, layering, combined Faraday rotation and optical activity, or a rotator-loaded optical cavity highlights their similarity and suggests alternate approaches to improving and miniaturizing optical devices.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 39 publications
0
7
0
Order By: Relevance
“…The underlying physics of CPA is a joint action of the system disspation and the destructive interference between the transmitted and reflected fields [2,4]. Due to wide potential applications [5][6][7] in optical communications and photonic devices such as transducers, modulators, optical switches and transistors, CPA has attracted considerable interest [2][3][4][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…The underlying physics of CPA is a joint action of the system disspation and the destructive interference between the transmitted and reflected fields [2,4]. Due to wide potential applications [5][6][7] in optical communications and photonic devices such as transducers, modulators, optical switches and transistors, CPA has attracted considerable interest [2][3][4][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…Recently it has been shown that the light fields coupled to an optical cavity with an intra-cavity absorber can be completely absorbed and no light can escape through the cavity [3][4][5][6][7][8]. Such a cavity-absorber system acts as a coherent perfect absorber and may be useful for a variety of fundamental studies and practical applications [9][10][11][12][13][14][15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…It has been enabled to control light in an efficient and coherent way. [18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33] Normally, the coherent perfect photon absorption is occurring when two or more coherent lights overlap, leading to a spatial redistribution of energy. In other words, it is based on the destructive interference between the input lights.…”
Section: Introductionmentioning
confidence: 99%